THE RELATIONSHIP BETWEEN KNOWLEDGE OF HIV/AIDS AND THE RISK OF TRANSMISSION OF HIV/AIDS IN ADOLESCENTS AT SENIOR HIGH SCHOOL 22 BEKASI CITY IN 2023 - Alfian, Rika; Deniati, Kiki; Meliyana, Ernauli (Rena Cipta Mandiri, 2023)
Background: Adolescence is the transition period from childhood to adulthood, secondary sexual characteristics begin to appear, there is a growth spurt, fertility is achieved, and cognitive and psychological changes occur. Adolescence is actually between childhood and adulthood, so the emotional state is unstable and the desire to try new things is very high, so adolescence is often referred to as a time of self-discovery. One aspect of the development of identity-seeking adolescents is the role of sexuality in developing relationships with peers. Adolescents sexual maturity results in adolescents becoming interested in the physical anatomy of their body. In addition to being attracted to oneself, there is also attraction to the opposite sex. This condition makses adolescents, including students, vulnerable to risky behavior problems, such as premarital sex that leads to unwanted pregnancies and substance abuse. (Prabasari et al., 2019). Research Objective: To determinate the relationship between knowledge about HIV/AIDS and the risk of HIV/AIDS transmission in adolescents at SMAN 22 Bekasi City 2023. Research Method: The research method carried out by researchers is quantitative. The research design in this study used observational analytics with a cross sectional design. Cross sectional is an analytical research design that aims to determine the relationship between variable where independent variables and dependent variables are identified at one time. Research Results: Based on statistical analysis with a significant level of 95% or a value of α 5% (0,05) obtained p value (0,000) α value (0,05), so that it can be concluded from these results H0 rejected means that there is a relationship between knowledge about HIV/AIDS and the risk of HIV/AIDS transmission in adolescents at SMAN 22 Bekasi City in 2023. Conclusion: H0 rejected means that there is a relationship between knowledge about HIV/AIDS and the risk of HIV/AIDS transmission in adolescents at SMAN 22 Bekasi City.